Pengembangan APE Bowling untuk Menstimulus Kemampuan Mengenal Lambang Bilangan Anak Usia 4-5 Tahun di TK Nasrani-2 Medan - Gaberiella U.T.R.Simatupang; Srinahyanti Srinahyanti (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The problem found in this research is that the bowling educational game tool used to stimulate the ability to recognize number symbols in children aged 4-5 years has not been realized. The formulation in this research is 1) What is the level of validity of APE Bowling to stimulate the ability to recognize number symbols in children aged 4-5 years at Kindergarten Nasrani 2 Medan? 2) What is the level of practicality of APE Bowling to stimulate the ability to recognize number symbols in children aged 4-5 years at Christian Kindergarten 2 Medan? . This research is development research using the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The method used in this research is using a questionnaire method. The results of the development research show that the material expert validator's assessment received a score of 93% so that the assessment achieved by the material expert can be said to be "very valid" while the average media expert validator assessment received a score of 80%, so that the media expert's assessment can be said to be "decent". and the assessment from educational practitioners is 98% which can be said to be "very practical". So by using the educational bowling game tool that has been developed, it can stimulate the recognition of number symbols 1-10 in children aged 4-5 years so that the ability to recognize number symbols in children aged 4- 5 years old at Kindergarten Nasrani-2 Medan, totaling 12 people, of which 5 boys and 7 girls increased.